Has collateral blood flow any effect on restenosis rate? Our experience - Li, Yanjiang; Sun, Yujie; Liu, Tonghui; Liu, Peng; Li, Guangwen; Zhang, Yong (Frontiers in Neurology, 2024)
Objectives: Restenosis is one of the important factors affecting the effectiveness of percutaneous transluminal angioplasty and stenting in the treatment of intracranial atherosclerotic stenosis. We aimed to clarify whether recruitable collateral flow could cause restenosis in patients treated with percutaneous transluminal angioplasty and stenting. Material and Methods: Our study retrospectively analyzed patients with symptomatic severe intracranial atherosclerotic stenosis (≥70%) who underwent percutaneous transluminal angioplasty and stenting. We enrolled 28 patients with restenosis and 71 patients without restenosis. We analyzed baseline data, perioperative events, and follow-up results of patients in the two groups. Binary logistic regression analysis was used to identify restenosis predictors. Results: For preoperative stroke, the restenosis group had a greater likelihood of having a previous stroke (89.3%), which was less prevalent in the non-restenosis group (66.2%) (P=0.020). The restenosis group had a higher rate of re-stroke (21.4% vs. 4.2%, P=0.022). After binary logistic regression analysis, collateral circulation and residual stenosis were independent risk factors of restenosis, with overall risk (95% confidence intervals) of 5.034 (1.484-4.066, P<0.001) and 1.064 (1.006-1.125, P=0.030), respectively. Restenosis risk increased 1.456-fold for each collateral circulation grade increase. However, for each 1% increase in residual stenosis, restenosis risk increased by 5.9% (P=0.03). The chance of restenosis is minimal when the residual stenosis rate after percutaneous transluminal angioplasty and stent implantation is 15.85%. Conclusions: Good collateral circulation was significantly associated with restenosis in patients undergoing intracranial angioplasty, the residual stenosis rate tends to be 15.85% to reduce restenosis risk. Compared to patients with restenosis, those without restenosis have a low stroke risk during follow-up.